Built environment factors and their impacts on outdoor walking activity among people living with dementia: a spatial analysis approach - Nouri, Mohammadjavad; Chaudhury, Habib (Frontiers in Public Health, 2025)
IntroductionAs the population of people living with dementia in Canada continues to grow, understanding the built environment’s role in facilitating outdoor activity is increasingly critical. While prior qualitative and quantitative research has established the benefits of outdoor walking for the physical, mental, and social well-being of people living with dementia, empirical spatial analysis of built environment factors influencing their walking behavior remains limited.MethodsThis study serves as a proof of concept, demonstrating the feasibility of applying spatial analysis to assess the impact of built environment variables on outdoor walking among people living with dementia. Using data from 25 participants in Metro Vancouver, this study integrates Geographic Positioning System (GPS) and Geographic Information System (GIS) tracking with exploratory factor analysis (EFA) and multiple linear regression (MLR) to examine the relationship between built-environment characteristics and walking distances.ResultsDespite the small sample size, statistical analyses met standard validity criteria, identifying three key factors influencing walking distance: (1) Macro environment—accessibility to public transportation and street network characteristics (p = 0.007, 439.6 m increase), (2) Micro environment—pedestrian-oriented design (p = 0.065, 286.5 m increase), and (3) General characteristics—mixed land use and sidewalk suitability (p = 0.015, 388.5 m increase).DiscussionThese findings provide preliminary evidence of the built environment’s role in shaping mobility for people living with dementia, offering valuable insights for public health policy makers, urban planners and designers, and transportation professionals in designing dementia-friendly neighborhoods. By integrating spatial analysis with environmental design principles, this study contributes to the development of inclusive and accessible urban environments for people living with dementia.